EXPLORING FACTORS THAT CAN AFFECT STUDENTS’ WORK READINESS - Sultoni, Sultoni; Gunawan, Imam; Mangzila, Asfi (Universitas Negeri Surabaya, 2023)
Work readiness can be thought of as the extent to which individuals have the attitudes and skills needed to be successful in their job. This study aims to explore the factors that can influence students’ work readiness. Data collected from 64 Bidikmisi scholarship recipients were analyzed using factor analysis. The results confirmed that the five proposed dimensions were reduced to two factors. The first factor consists of three dimensions namely maturity level, mental and emotional state, and self-development efforts. The second factor consists of two dimensions namely previous experience and intelligence level. Implications of the findings are discussed and future research opportunities are suggested.